1994
DOI: 10.1017/s0033291700027781
|View full text |Cite
|
Sign up to set email alerts
|

The differentiation of depression from dementia by temporal lobe magnetic resonance imaging

Abstract: SynopsisTemporal lobe Magnetic Resonance Imaging (MRI) was performed in 43 patients with NINCDS/ADRDA Alzheimer's disease (AD) (33 probable, 7 possible, 3 definite) and 32 subjects with DSM-III-R Major Depression (DEP) matched for age, sex and level of education. Hippocampus (anterior and posterior, right and left), amygdala, entorhinal cortex, para-hippocampal gyrus and cerebral cortex were rated for atrophy on a 4-point scale. Good discrimination between groups could be achieved using a cut-off of 2 or more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 34 publications
3
41
1
2
Order By: Relevance
“…In schizophrenia, Chua and McKenna (1995) reviewed 14 MRI investigations that measured the amygdala-hippocampal complex; five found diminution in both hippocampus and amygdala, three in hippocampus only, and six in neither. Hippocampal atrophy has not been found in depressives (Axelson et al 1993), even those with cognitive impairment (O'Brien et al 1994), nor in alcoholic Korsakoff's syndrome (Squire et al 1990). Gurvits et al (1993) reported neurologic compromise in Vietnam veterans with PTSD, manifested by increased neurologic soft signs and a history of neurodevelopmental abnormalities.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In schizophrenia, Chua and McKenna (1995) reviewed 14 MRI investigations that measured the amygdala-hippocampal complex; five found diminution in both hippocampus and amygdala, three in hippocampus only, and six in neither. Hippocampal atrophy has not been found in depressives (Axelson et al 1993), even those with cognitive impairment (O'Brien et al 1994), nor in alcoholic Korsakoff's syndrome (Squire et al 1990). Gurvits et al (1993) reported neurologic compromise in Vietnam veterans with PTSD, manifested by increased neurologic soft signs and a history of neurodevelopmental abnormalities.…”
Section: Introductionmentioning
confidence: 97%
“…It has, for example, been reported in 33% of MRIs in normal elderly persons (Golomb et al 1993). Hippocampal atrophy has also been proposed as an early marker for Alzheimer's disease (Desmond et al 1992;O'Brien et al 1994). In schizophrenia, Chua and McKenna (1995) reviewed 14 MRI investigations that measured the amygdala-hippocampal complex; five found diminution in both hippocampus and amygdala, three in hippocampus only, and six in neither.…”
Section: Introductionmentioning
confidence: 99%
“…De 1990 a 1995, vários autores 9,16,[20][21][22][23][24][25] buscaram saber quais os idosos deprimidos que apresentam hipersinais à ressonância magnética. Embora os estudos apresentassem resultados conflitantes, algumas características se repetiam.…”
Section: Discussionunclassified
“…This similarity stands in contrast to a report comparing forgetting rates for line drawings over longer (10 min-48 h) intervals, with depressives being unimpaired in comparison with controls 36 . This article focuses on those neuropsychological approaches which are attempting to distinguish the cognitive impairments of such patients from those of patients with DAT and may augment other tests, such as MRI 44 . An obvious way to establish the causal status of the cognitive deficits is to study them longitudinally, when many elderly depressed patients exhibit clinical recovery as a consequence of medication or other forms of therapy (Fig.…”
Section: Cognitive Deficits In Depressionmentioning
confidence: 99%